Effect of Impurities and LiF Additive in Hot‐Pressed Transparent Magnesium Aluminate Spinel. (29th August 2012) - Rubat du Merac, Marc; Reimanis, Ivar E.; Smith, Charlene; Kleebe, Hans‐Joachim; Müller, Mathis M.
Abstract : The effect of impurities and LiF sintering additive on the microstructure and optical properties of hot‐pressed transparent MgAl2 O4 spinel was investigated. A lower and a higher purity powder were hot pressed with and without LiF and process parameters varied. Microstructure was examined using optical and electron microscopy, optical properties using spectrophotometry, and chemistry using various spectroscopic techniques. Impurities present in parts‐per million were found to segregate at grain boundaries and form an amorphous phase, restricting grain growth and causing scatter and opacity. It was found that LiF reacts with impurities to form volatile species that can be removed with proper processing, resulting in larger grain size and increased transmittance. LiF also counteracts absorption caused by reduction of spinel, but results in MgO loss, grain boundary embrittlement, and if trapped in higher concentration, restricts grain growth and causes scatter and opacity.